Electroactive Polymer Actuators and Devices (EAPAD) 2008 2008
DOI: 10.1117/12.777900
|View full text |Cite
|
Sign up to set email alerts
|

A dielectric elastomer actuator with self-sensing capability

Abstract: In this paper we present a dielectric elastomer actuator, which has the ability to sense the force acting on it without any additional sensing device. Basic physical behaviors of the dielectric elastomer are experimentally investigated and it is noted that the impedance of the dielectric elastomer varies depending on external forces acting on it. Based on that concept, we propose the principle of a self-sensing actuator according to experimental result. In addition, a multi-stacked actuator with self-sensing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The flexible actuators are expected to be used as electrical switches for flexible supercapacitor, lithium-ion battery, and other electrochromatic devices. , However, general designs of flexible actuators are based on all-organic or organic/inorganic composite materials, usually subject to slow response, limited lifetime, or high triggering threshold. Ionic electroactive polymer (ionic EAP), electronic EAP, and thermally active polymer are major actuation materials for flexible actuators based on various driving mechanisms. , Most of ionic EAP have low driving voltages (∼several volts), yet their responses are typically slow, in the range of 0.1–10 s. The response time of thermally active polymers is limited by their low thermal conductivity, as a result usually larger than 0.1 s. Electronic EAP could respond as fast as down to ∼1 ms, whereas their high driving voltages usually over 1 kV have greatly limited the range of their applications. Therefore, it is still a great challenge to build flexible actuators, which could rapidly respond to multiple stimuli, with low requirements for driving conditions.…”
mentioning
confidence: 99%
“…The flexible actuators are expected to be used as electrical switches for flexible supercapacitor, lithium-ion battery, and other electrochromatic devices. , However, general designs of flexible actuators are based on all-organic or organic/inorganic composite materials, usually subject to slow response, limited lifetime, or high triggering threshold. Ionic electroactive polymer (ionic EAP), electronic EAP, and thermally active polymer are major actuation materials for flexible actuators based on various driving mechanisms. , Most of ionic EAP have low driving voltages (∼several volts), yet their responses are typically slow, in the range of 0.1–10 s. The response time of thermally active polymers is limited by their low thermal conductivity, as a result usually larger than 0.1 s. Electronic EAP could respond as fast as down to ∼1 ms, whereas their high driving voltages usually over 1 kV have greatly limited the range of their applications. Therefore, it is still a great challenge to build flexible actuators, which could rapidly respond to multiple stimuli, with low requirements for driving conditions.…”
mentioning
confidence: 99%
“…The self-sensing DE actuator has been designed and investigated extensively [151 -158]. Furthermore, numerous studies have reported this by measuring capacitance during actuation to monitor the change in strain [158][159][160][161]. This design paves the way for micro-scale actuators, since independent sensing devices are not needed.…”
Section: Sensors Based On Dielectric Elastomersmentioning
confidence: 99%
“…The self-sensing methods in previous publications differ from each other regarding the analyzed electrical characteristics, like electrode resistance 8 , leakage current 9,10 , different concepts of capacitance measurements 11,12,13 or even combinations of them 14,15 . However, in most cases only one of these parameters is analyzed, while other parameters are taken as constant or even negligible, which can lead to serious reduction of accuracy 14 .…”
Section: Introductionmentioning
confidence: 98%